2014
DOI: 10.1002/hed.23683
|View full text |Cite
|
Sign up to set email alerts
|

Utility of magnifying endoscopy with narrow band imaging in determining the invasion depth of superficial pharyngeal cancer

Abstract: ME-NBI is useful to determining invasion depth of superficial pharyngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…This issue is still under debate; a pathological study by Fujii et al suggested that there is a positive correlation between tumor microvascular morphology and the depth of tumor invasion in HNSCC. The study results of Kikuchi et al support this finding. Because ELPS is conducted in collaboration with esophageal surgeons at our institute, tumor microvessel morphological evaluation based on the JES classification is already applied in our routine practice with excellent local control and low complication rates.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This issue is still under debate; a pathological study by Fujii et al suggested that there is a positive correlation between tumor microvascular morphology and the depth of tumor invasion in HNSCC. The study results of Kikuchi et al support this finding. Because ELPS is conducted in collaboration with esophageal surgeons at our institute, tumor microvessel morphological evaluation based on the JES classification is already applied in our routine practice with excellent local control and low complication rates.…”
Section: Discussionmentioning
confidence: 57%
“…In esophageal cancer, prediction of the depth of tumor invasion and indication of ESD are determined using magnifying endoscopy with narrowband imaging (ME‐NBI). The esophagus and pharynx are both composed of squamous epithelium; ME‐NBI is therefore considered effective for head and neck squamous cell carcinoma (HNSCC) . Prediction of the depth of tumor invasion using ME‐NBI is based on microvessel morphology, which is well studied in esophageal cancer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] In this video article, we describe the endoscopic diagnosis and treatment of superficial pharyngeal cancer. Such cancers have been treated by invasive surgery and chemoradiotherapy.…”
Section: Brief Explanationmentioning
confidence: 99%
“…Recent developments in narrowband imaging with magnified endoscopy (NBI-ME) and medical image processing technologies allow clear visualization of the esophageal microvascular structure, facilitating cancer detection in the early stage [24, 25]. …”
Section: Related Workmentioning
confidence: 99%